Politik Hukum Mengenai Keterbukaan Data Medis Tenaga Medis Penderita COVID-19 VS Transparansi Informasi Publik Sebagai Bentuk Perlindungan Hukum Universal - Yohanes Firmansyah; Muhammad Ali Hanafiah Selian (Yayasan Pendidikan Medika Indonesia, 2022)
The Covid-19 case has become a pandemic and a major problem throughout the world, especially Indonesia due to its very easy and fast spread from person to person. These medical problems directly affect social life, especially legal issues that cause friction between the confidentiality of patient data as a form of private law and the disclosure of public information as a form of modern society's demands for open, actual, and transparent information. This research is a study that reviews normative juridical by means of analysis and synthesis of deductive conclusions from various statements in various secondary data sources which are all relevant and related to the main issues discussed in this journal with the aim of obtaining an overview of legal reviews and comparative studies related to this issue. . A literature search reveals the principle of legal certainty and legal protection for the community, especially in the era of the Covid-19 pandemic. The status of medical records is also a part of private legal aspects that are confidential and may not be disseminated to the general public without the permission of the owner or legislation. However, in the era of the Covid-19 pandemic, accompanied by the public's encouragement of public information disclosure, the principle of public interest must be guaranteed by the rule of law, by demonstrating a strong commitment to the principle of